(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Proton exchange membrane fuel cell (PEMFC) is one of the most energy-efficient and energy-dense devices. PEMFC technology is outstanding due to its high durability, performance, dependability, and low unit price. PEMFC is comprised of multiple components that are susceptible to damage, resulting in system failure. Component functionality can degrade during the design process, during assembly, or during operation. Gradual component failure will lead to mechanical failure, which can result in unit damage and incapacity to operate. PEMFC's acceptance as a commercially sophisticated technology is hindered in part by its susceptibility to mechanical failure. Therefore, it is vital to comprehend and analyze the failure mechanism of frequently failing components based on the unit's arrangement in order to reduce component failure in the future through the design and development of new components.